VALIDITAS KLINIK GENERAL HEALTH QUESTIONNAIRE-12 SEBAGAI INSTRUMEN SKRINING GANGGUAN INSOMNIA PRIMER DI PUSKESMAS - , Novita; , Rahmat Hidayat, S. Psi, M. Sc, Ph. D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sleep disorder is one of the seven highest prevalence disorders in primary care (Puskesmas). Primary insomnia is sleep disorderâs subtype which frequently diagnosed. Despite itâs prevalence, which is 6%, most of patient with primary insomnia were unidentified. This research is aimed to test the clinical validation of GHQ-12 as an efficient screening tool for primary insomnia in primary care setting. The result of clinical interview based on Diagnostic and Statistical Manual of Mental Disorder IV Text Revision (DSM-IV-TR) held by trained psychologists is used as gold standar. There were 227 adult subjekts age 18-60 from ten Puskesmasâs in Sleman dan Yogyakarta, Yogyakarta Province. There were 0.44% patient diagnosed have primary insomnia. Psychometric tests showed the datas were reliable to be analyzed (Alpha Cronbach = 0.945) and GHQ-12 is unidementional instrument based on Principal Component Analysis. Concurrent validity coefficient (r = 0.16) and diagnostic test (AUC = 58%